2020
DOI: 10.1186/s12906-020-03049-5
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of microbial cell morphology by Buxus macowanii

Abstract: Background: Microbial infections are one of the major causes of death globally. This is attributed to the rising costs of primary healthcare and its inaccessibility especially in developing countries. Moreover, there has been an increase in microbial strains that have reduced susceptibility to antimicrobial drugs. Research on the antimicrobial properties of medicinal plants, which could address these problems, has become more important as they present fewer side effects when compared to the antibiotics current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…pneumoniae still remains undetermined in this study. A study also reported that plant extract induces various effects on bacteria including bacterial lysis, cell wall disorder, swelling, and cell division anomaly which were reported on Bacillus cereus treated with extract of Buxus macowanii [ 58 ]. Moreover, detection of DNA or RNA released by cells into media was not able to determine bacterial leakage caused by plant extract since we found inconsistent data obtained overtime due to nucleotide degradation (DOI: 10.6084/m9.figshare.20364249 ).…”
Section: Discussionmentioning
confidence: 99%
“…pneumoniae still remains undetermined in this study. A study also reported that plant extract induces various effects on bacteria including bacterial lysis, cell wall disorder, swelling, and cell division anomaly which were reported on Bacillus cereus treated with extract of Buxus macowanii [ 58 ]. Moreover, detection of DNA or RNA released by cells into media was not able to determine bacterial leakage caused by plant extract since we found inconsistent data obtained overtime due to nucleotide degradation (DOI: 10.6084/m9.figshare.20364249 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other medicinal herbs that have anti-microbial activity also contain substances found in neem extract. This includes such as ÎČ-Bourbonene ( 28 ), ÎČ-copaene, ÎČ-caryophyllene ( 29 ), ÎŽ-Cadinene ( 30 ), Neophytadiene ( 31 ). Moreover, some substances in neem, such as Îł-Muurolene, has anti-nociception property in tested animal models ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Three plant extracts with 0.02 mg/mL MIC values were found in X. zambesiaca, M. zeyheri, and A. grandiflora, followed by E. transvaalense with two plant extracts with excellent antibacterial activity. Traditional health practitioners employ the boiled stem and roots of X. zambesiaca to cure stomach symptoms and 'Nyoko', a gall bladder dysfunction (Ngobeni 2016). Furthermore, it is used in traditional remedies to treat diabetes and gastrointestinal problems.…”
Section: Plant Extracts With Excellent Antibacterial Activitymentioning
confidence: 99%